PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DAN KESETIAAN MEREK PADA PRODUK TOLAK ANGIN CAIR SIDOMUNCUL - Dhewi Andria Darnawati; Aftoni Sutanto (Universitas Ahmad Dahlan, 2012)
This study aims to determine how the effect of product quality to customer satisfaction and customer loyalty on the product Tolak Angin Cair Sidomuncul and to find out what is the most dominant variable affecting consumer satisfaction and brand loyalty to the product of Tolak Angin Cair Sidomuncul. The population in this study is that people in the District of Umbulharjo, the city of Yogyakarta. Sampling techniques used is incidental sampling. Sources of data from this study using primary data obtained from the deployment questionnaire. This study used data analysis techniques are qualitative and quantitative analysis (multiple regression analysis, t test and F test). T test results on customer satisfaction (Y1) show that for each of the performance variables (X1), Reliability (X2), Endurance (X3), Aesthetics (X4), and perceived quality (X5) obtained the calculated value of t-count> t-table. It can be concluded that the performance variables (X1), aesthetics (X4), the perceived quality (X5), the partial effect is not significant and, while the variables Reliability (X2), Endurance (X3) and significant effect on customer satisfaction and t test results on brand loyalty disimpilkan that performance (X1), Reliability (X2), Endurance (X3), Aesthetics (X4), partial and no significant effect, whereas the perceived quality variables (X5) of consumerÂ loyalty to the product Tolak Angin Sidomuncul. The results of the F test, F-table obtained Â = 5% F-count on the consumer satisfaction of 7.420. While the F-count on brand loyalty of 16.728. Because the F-count value. F-table, then the performance of independent variables (X1), Reliability (X2), Endurance (X3), Aesthetics (X4), and perceived quality (X5) simultaneously affect consumer satisfaction and brand loyalty to the product of Tolak Angin Cair Sidomuncul.